Water for the environment from policy and science to implementation and management - Horne, Avril C.; Webb, J. Angus; Stewardson, Michael J.; Richter, Brian; Acreman, Mike (London Academic Press, 2017)
Water for the Environment: From Policy and Science to Implementation and Management provides a holistic view of environmental water management, offering clear links across disciplines that allow water managers to face mounting challenges. The book highlights current challenges and potential solutions, helping define the future direction for environmental water management. In addition, it includes a significant review of current literature and state of knowledge, providing a one-stop resource for environmental water managers.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Water-supply -- Environmental aspects; Water-supply -- Management; Electronic books